Beckon the dragon: How businesses can attract the Chinese consumers through digital marketing - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
The rise of China to the world’s second largest economy has seen a boom in its consumer market with its citizens having more purchasing power. China’s retail market is growing rapidly, including the trend of online shopping with the expansion of the credit card industry. As more and more Chinese citizens get online, the internet is slowly becoming a powerful tool for businesses to reach out to them.